The Role of Islamic Economics in Managing Wealth and Curbing the Culture of Hedonism to Achieve Maximum Utility - Eli Febriani; Yerna Wiza; Fofi Hanifa Seftiani; Ferdi Prayoga; Iiz Izmuddin (Universitas 17 Agustus 1945 Semarang, 2025)
The crazy rich phenomenon as a form of modern materialism and hedonism has poisoned the lives of the young generation of Indonesia in the current millennial era. They have been eroded by worldly pleasures. Tempted by the glamorous and luxurious lifestyle of the crazy rich, they are willing to show off their wealth that is not actually theirs. The purpose of this study is to determine wealth in the Islamic perspective. Qualitative research methods with a descriptive approach are sourced from literature study data. Wealth should be used for social interests, such as through zakat, alms, and fair economic activities. Islam emphasizes the importance of using wealth responsibly to meet basic needs and improve people's welfare, without forgetting simplicity as the main principle. Wealth must be obtained and used in a halal way, not for things that are in vain or violate sharia, and support the values of justice and blessings.